SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PENGGUNAAN JENIS TANAMAN DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Nur Musyarrofatul Mala; Anton Muhibuddin; Agus Sifaunajah (SAINTEKBU, 2018)
Agriculture is an important sector that can not be separated in determining the formation of various economic and social reality of society in various regions of Indonesia. Most of the livelihoods of the Indonesian community are covered by agriculture. In daily life for farmers there are still many problems or constraints such as crop failure due to less suitable land for plant growth, climate uncertainty and others. So in this case will be made information system that will provide recommendations for farmers in determining the use of plant species in accordance with the conditions of land in certain areas.This application use the Analytic Hierarchy Process (AHP) as a method that will take the decision of some criteria by calculating the weight ratio or value on each type of plant and will produce information in the form of cropratings are recommended. So that decision support system with AHP method can be used as one solution in solving the problem of choosing the use of plants in accordance with the condition of the land in certain areas. Keywords: Analytic Hierarchy Process (AHP), Decision Support System, Land Suitability